The crystal structure of fac-tricarbonyl(6-bromo-2,2-bipyridine-κ2 N,N)-(nitrato-κO)rhenium(I), C13H7BrN3O6Re - Mkhatshwa Marcus; Malan Frederick P.; Makgopa Katlego; Manicum Amanda-Lee E. (Zeitschrift für Kristallographie - New Crystal Structures)
C13H7BrN3O6Re, monoclinic, P21/n (no. 14), a = 7.2645(1) Å, b = 10.0607(1) Å, c = 20.7717(2) Å, β = 97.1800(10)°, V = 1506.22(3) Å3, Z = 4, R gt(F) = 0.0359, wR ref(F 2) = 0.0810, T = 150 K.